Excellence of the diversity value and the educational environment on student nationalism - Rukiyati Rukiyati; Farida Hanum; L. Andriani Purwastuti (Jurnal Cakrawala Pendidikan, 2023)
This study aimed at determine the role of the diversity value and the educational environment on Indonesian student nationalism. A quantitative approach was used with descriptive and inferential regression methods, while the populations were all Indonesian students at public and private universities. Furthermore, the samples consisted of 916 respondents obtained through purposive sampling covering the clusters of Eastern Indonesia, namely NTB and NTT, the Central, which include Kalimantan, and that of West, namely Java and Sumatra. The data were collected through a questionnaire that was tested for validity and reliability, while the instrument was analyzed using the EFA technique and the hypothesis was tested through regression analysis with SEM program. It was discovered that the diversity value and the educational environment had a significant role in the knowledge, attitudes, and behavior of Indonesian student nationalism, such that an increase in the educational environment also leads to the improvement of nationalism attitude. Similarly, the diversity value had a positive significant effect on the Indonesian student nationalism knowledge and attitude. This means that its increase results in improved knowledge of nationalism. Therefore, this study has been able to prove that the fear of a decline in student nationalism is irrelevant.